Stories of taking part in Everyday Life Rehabilitation - A narrative inquiry of residents with serious mental illness and their recovery pathway - Rosaline Bezerra Aguiar; Maria Lindström (AIMS Public Health)
Context and purposePersons enduring serious mental illness (SMI) and living in supported housing facilities often receive inadequate care, which can negatively impact their health outcomes. To address these challenges, it is crucial to prioritize interventions that promote personal recovery and address the unique needs of this group. When developing effective, equitable, and relevant interventions, it is essential to consider the experiences of persons with an SMI. By incorporating their perspectives, we can enhance the understanding, and thereby, the design and implementation of activity- and recovery-oriented interventions that promote health, quality of life, and social connectedness in this vulnerable population. Thus, the aim of this study is to explore the stories of participants partaking in Everyday Life Rehabilitation and how they make sense of their engagements in everyday life activities and their recovery processes.MethodsApplying a narrative analysis, this study explores the stories of seven individuals with an SMI residing in Swedish supported housing facilities, participating in the Everyday Life Rehabilitation (ELR) program during six months, and how they retrospectively make meaning of their engagement in everyday life activities and recovery processes.FindingsThe participants' stories about their rehabilitation and personal recovery pathways elucidate how the inherent power of the activity, as well as the support the participants received to get started and succeed, had a significant impact on their self-identity, confidence, motivation, mattering, life prospects, and vitality. The participants valued the transparent steps along the process, weekly meetings, the signals, beliefs, and feedback communicated throughout, and the persistent, adaptive, and yet supporting approach in their personal progress.SignificanceThis study underscores the need for interventions that prioritize meaningful activities and are sensitive to the complexity of the personal recovery process, especially in supported housing facilities. Future research should further explore effective strategies and mechanisms to promote personal recovery and to reduce the stigma associated with SMI.